Hyposmolality differentially and spatiotemporally modulates levels of glutamine synthetase and serine racemase in rat supraoptic nucleus. Issue 4 (30th January 2013) - Wang, Yu‐Feng; Sun, Min‐Yu; Hou, Qiuling; Parpura, Vladimir
Abstract Prolonged hyposmotic challenge (HOC) has a dual effect on vasopressin (VP) secretion [Yagil and Sladek (1990) Am J Physiol 258(2 Pt 2):R492‐R500]. We describe an electrophysiological correlate of this phenomenon, whereby in vitro HOC transiently reduced the firing activity of VP neurons within the supraoptic nucleus of brain slices, which was followed by a rebound increase of their activity; this was paralleled by changes in the level of proteins relevant to astroglia–neuronal interactions. Hence, in vitro HOC transiently (at 5 min) increased the level of astrocyte‐specific glial fibrillary acidic protein (GFAP), which then declined to control or base level (at 20 min); this was blocked by the gliotoxin L‐aminoadipic acid, but not by tetanus toxin, which was used to inhibit neurotransmission. Similarly, in vivo HOC led to changes in GFAP level, which after an early increase (10 min) returned to normal (30 min). Immunoassays revealed that neuronal, but not astrocytic, expression of serine racemase (SR) was increased at the late stage of HOC in vivo, whereas at an early stage there was a transient increase in level of the astrocyte‐specific glutamine synthetase (GS). Furthermore, there was an increased molecular association between GFAP and GS at 10 min, whereas SR increased its association with the neuronal nuclear antigen NeuN at 30 min. These results suggest that the dual effect of HOC on VP neuronal secretion/activity could be related to metabolic/signaling changes in astrocytes (glutamate–glutamine conversion) and neurons (D‐serine synthesis/ammonia production), which may account for the rebound in VP neuronal activity, presumably by promoting the activation of neuronal glutamate receptors. © 2013 Wiley Periodicals, Inc.